Penerapan Pendekatan Manual Dexterity Untuk Meningkatkan Keaktifan Siswa Kelas IV SD Negeri 0501 Hutanopan - Siti Asrina Harahap; Mancar Mancar; Lina Maya Sari Siregar (CV. Aksara Global, 2023)
The aim of this research is to determine the application of learning in class IV of SD Negeri 0501 Hutanopan using a manual dexterity approach to student activity. The type of research used is classroom action research. Based on the research results, it can be concluded that in cycle I an increase in student learning activity had occurred but was not optimal. However, in cycle II there was quite a good improvement until it reached the completeness expected by the researchers. Increased student learning activity, namely in the pre-cycle student activity in the